2005
DOI: 10.1016/j.ymthe.2005.03.034
|View full text |Cite
|
Sign up to set email alerts
|

RNA Transfer by Electroporation into Mature Dendritic Cells Leading to Reactivation of Effector-Memory Cytotoxic T Lymphocytes: A Quantitative Analysis

Abstract: Previous studies have analyzed transfer of RNA-encoded tumor-associated antigens (TAAs) into immature dendritic cells (DCs) because of their exceptional ability to internalize antigens. Concerns have been raised regarding the use of immature DCs in clinical studies because of their capacity to tolerize T cells. Therefore, we focused on optimizing RNA transfer into mature DCs using the method of electroporation and obtained high protein expression in 90% of mature DCs. Particular emphasis was placed on quantify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 30 publications
2
42
0
Order By: Relevance
“…Prior or concurrent maturation of human monocyte-derived DC with CD40L did not alter nucleofection efficiency with either DNA or mRNA in our studies, similar to results in previous reports (29,34), although in other studies, electroporation of mRNA into mature DC led to a modest increase in transgene expression (22). Larregina et al reported that simultaneous transfection and CD40-mediated maturation of murine bone marrow-derived DC significantly enhanced DNA transfection efficiency (28), suggesting that maturation may have a greater effect on gene expression in the murine system.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Prior or concurrent maturation of human monocyte-derived DC with CD40L did not alter nucleofection efficiency with either DNA or mRNA in our studies, similar to results in previous reports (29,34), although in other studies, electroporation of mRNA into mature DC led to a modest increase in transgene expression (22). Larregina et al reported that simultaneous transfection and CD40-mediated maturation of murine bone marrow-derived DC significantly enhanced DNA transfection efficiency (28), suggesting that maturation may have a greater effect on gene expression in the murine system.…”
Section: Discussionsupporting
confidence: 91%
“…This discrepancy between our results and those of others using electroporation might be explained by the use of different electroporation devices leading to differences in the delivery of electric current to cells. In our studies, the efficiency of nucleofection was such that as little as 5 g mRNA resulted in near-total transfection of DC, yet at least 50 g mRNA can be safely delivered to DC without apparent toxicity (22). This provides the advantage of being able to introduce relatively small amounts of mRNA encoding multiple genes into DC simultaneously, such as different patient-derived viral genes for immunotherapy of HIV infection.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Subsequent studies have highlighted that DCs electroporated after maturation were at least as efficient in antigen presentation and had even greater potency to invoke immune response than DCs electroporated before maturation [12,45,46]. We further expand on Numerous studies have demonstrated a correlation between antigen persistence in the DC and magnitude of the immune response [47][48][49].…”
Section: Immunity 2002mentioning
confidence: 82%